O LUGAR COMPLEXO DO LEITOR NO JORNALISMO CONTEMPORÂNEO: potencialidades, limites, dilemas e o caso do jornal O Globo - Mendes, Larissa de Morais Ribeiro (2012)
This study proposes a reflection on the complex implications of reader participation for modern journalism, in the context of the interactive possibilities that arise with the internet and new information technology. Journalistic companies live in a state of permanent tension with their public: they need participation, but they fear losing control over it, for legal, ideological and market reasons. The question involves the very survival of the companies, in a struggle to decide who is legitimately entitled to inform in an age when anyone can disseminate information. In this turbulent arena, the discussion centers on what the participation of the reading public can effectively contribute to make journalistic practices more inclusive and broad-based, and what risks are incurred by failing to go beyond simple discourse. Questions arise whether debates in the fields of commentary are superficial or whether they can deepen comprehension of the news. The body of analysis was culled basically from the on-line edition of the daily O Globo, although the question of labor extrapolates a case study. Throughout the study, two distinct moments were evident in relation to the paper and its readers. After an initial phase of enthusiasm and experimentation at the end of the past decade, O Globo is now regrouping, as evidenced by the reformulation of its site, on the air since November 2011